Expression of PR genes and genes of heat shock proteins of potato plants in vitro under infection with ring rot and heat stress - Nurminsky, V.N.; Stolbikov, A.S.; Pomortsev, A.V.; Perfileva, A.I. (Вiopolymers and Cell, 2018)
Aim. The changes in expression of the HSP101, HSP60, and HSP17.8 genes in tissues of potato plants of varieties Lukyanovsky under in vitro heat treatment and infection with a ring rot pathogen Clavibacter michiganensis ssp. sepedonicus (Cms) were investigated. Methods. These changes were assessed at the transcript and protein levels. Results. It was shown that under heat treatment at 39°C for 2 h, the maximum accumulation of HSP101 was observed. In control experiments, the plants of the two varieties showed neither synthesis of HSP101, HSP60 and HSP17.8 proteins nor expression of the HSP101, HSP60 and HSP17.8 genes. Infection without heat treatment induced HSP60 expression. Infection suppressed activation of HSP genes upon heat stress. Additionally, infection of potato plants by Cms caused an increase in transcription of PR-2 and PR-4 genes. Conclusions Мета. Дослідити зміну експресії білків теплового шоку БТШ101, БТШ 60 і БТШ 17.8 в тканинах картоплі сорту Лук’яновський in vitro при тепловому впливі та зараженні збудником кільцевої гнилі Clavibacter michiganensis ssp. sepedonicus (Cms). Методи. Зміну експресії вивчено на двох рівнях: кількості транскриптів та вмісту протеїну. Результати. Показано, що при тепловому впливі 39 оС протягом 2 годин in vitro спостерігається максимальне накопичення HSP101. В контрольних варіантах у рослин було не було відмічено ані синтезу білків HSP101, HSP60 й HSP17.8, ані утворення транскриптів генів HSP101, HSP60 та HSP17.8. Зараження без теплового впливу індукувало експресію білку HSP60 в рослинах сорту Лук’яновський. Зараження пригнічувало активацію експресії БТШ при тепловому стресі. При зараженні рослин картоплі Cms підвищувалась кількість транскриптів генів PR-2 та PR-4. Висновки. Цель. Исследовать изменение экспрессии БТШ101, БТШ60 и БТШ17.8 in vitro в тканях картофеля сорта Лукьяновский при тепловом воздействии и заражении возбудителем кольцевой гнили Clavibacter michiganensis ssp. sepedonicus (Cms). Методы. Изменение экспрессии изучено на двух уровнях: количества транскриптов и содержании белка. Результаты. Было показано, что при тепловом воздействии 39 оС 2 часа в картофеле наблюдается максимальное накопление HSP101. В контрольных вариантах у растений не было отмечено ни синтеза белков HSP101, HSP60 и HSP17.8, ни образования транскриптов генов HSP101, HSP60 и HSP17.8. Заражение без тепловой обработки индуцировало экспрессию белка HSP60 в растениях сорта Лукьяновский. Заражение подавляло активацию экспрессии БТШ при тепловом стрессе. При заражении растений картофеля Cms повышалось количество транскриптов генов PR-2 и PR-4. Выводы.